2017
DOI: 10.1038/s41598-017-13621-8
|View full text |Cite|
|
Sign up to set email alerts
|

Dual contribution of TRPV4 antagonism in the regulatory effect of vasoinhibins on blood-retinal barrier permeability: diabetic milieu makes a difference

Abstract: Breakdown of the blood-retinal barrier (BRB), as occurs in diabetic retinopathy and other chronic retinal diseases, results in vasogenic edema and neural tissue damage, causing vision loss. Vasoinhibins are N-terminal fragments of prolactin that prevent BRB breakdown during diabetes. They modulate the expression of some transient receptor potential (TRP) family members, yet their role in regulating the TRP vanilloid subtype 4 (TRPV4) remains unknown. TRPV4 is a calcium-permeable channel involved in barrier per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
41
4
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(51 citation statements)
references
References 134 publications
(205 reference statements)
3
41
4
3
Order By: Relevance
“…In both diabetic and nondiabetic mice, the right eye was injected with vehicle (PBS) and the left eye received GSK2193874 (17.3 pg, corresponding to 50 nM, as the estimated volume of mouse vitreous is 4.4 μl (Kaplan et al, 2010)). We previously demonstrated that PBS is an acceptable vehicle (Arredondo Zamarripa et al, 2017). Intravitreal injection was performed 24 hours before the end of the 4 weeks of diabetes to mimic a treatment scheme.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…In both diabetic and nondiabetic mice, the right eye was injected with vehicle (PBS) and the left eye received GSK2193874 (17.3 pg, corresponding to 50 nM, as the estimated volume of mouse vitreous is 4.4 μl (Kaplan et al, 2010)). We previously demonstrated that PBS is an acceptable vehicle (Arredondo Zamarripa et al, 2017). Intravitreal injection was performed 24 hours before the end of the 4 weeks of diabetes to mimic a treatment scheme.…”
Section: Methodsmentioning
confidence: 99%
“…Eyes were then cryopreserved at 4 °C for 1 h 30 in 10 % and 20 % sucrose, respectively, in 30 % sucrose overnight, embedded in Tissue-Tek and frozen with liquid nitrogen. Cryostat was sectioned at 14 μm and mounted on slides for hematoxylin and eosin staining (Arredondo Zamarripa et al, 2017). Retinal layer thickness was quantified, as previously described (Arredondo Zamarripa et al, 2017).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations